Off-label use of tocilizumab for the treatment of SARS-CoV-2 pneumonia in Milan, Italy - Morena, Valentina (Eur J Intern Med, 2020)
BACKGROUND: Tocilizumab, a humanized monoclonal antibody, targets IL-6 receptors blocking downstream pro-inflammatory effects of IL-6. In preliminary reports it was suggested to be beneficial in patients with severe COVID-19. METHODS: In this open-label prospective study we describe clinical characteristics and outcome of 51 patients hospitalized with confirmed and severe COVID-19 pneumonia treated with tocilizumab intravenously. All patients had elevated IL-6 plasma level (>40 pg/mL) and oxygen saturation <93% in ambient air. Clinical outcomes, oxygen support, laboratory data and adverse events were collected over a follow-up of 30 days. RESULTS: Forty-five patients (88%) were on high-flow oxygen supplementation, six of whom with invasive ventilation. From baseline to day 7 after tocilizumab we observed a dramatic drop of body temperature and CRP value with a significant increase in lymphocyte count (p<0.001). Over a median follow-up time of 34 days from tocilizumab, 34 patients (67%) showed an improvement in their clinical severity class; 31 were discharged; 17 (33%) showed a worsening of their clinical status, of these 14 died (27%). The mortality rate was significantly associated with mechanical ventilation at baseline (83.3% vs 20% of patients on non-invasive oxygen support; p=0.0001). The most frequent side effects were an increase of hepatic enzymes (29%), thrombocytopenia (14%), and serious bacterial and fungal infections (27%). CONCLUSION: Tocilizumab exerts a rapidly beneficial effect on fever and inflammatory markers, although no significant impact on the clinical outcome can be inferred by our results. Critically ill patients seem to have a high risk of serious infections with this drug.